Prenatal ultrasound evaluation of fetal Hb Bart's disease among pregnancies at risk at 11 to 14 weeks of gestation. (20th December 2013) - Sirichotiyakul, Supatra; Luewan, Suchaya; Srisupundit, Kasemsri; Tongprasert, Fuanglada; Tongsong, Theera
ABSTRACT Objective The objective of this article is to evaluate the efficacy of the first trimester sonomarkers (11–14 weeks) in predicting hemoglobin (Hb) Bart's disease among fetuses at risk Materials and Methods Prospective analysis was conducted on pregnancies at risk of fetal Hb Bart's disease at 11 to 14 weeks of gestation. Sonographic markers including cardiothoracic (CT) ratio, peak systolic velocity of the middle cerebral artery (MCA‐PSV), placental thickness, and nuchal translucency were prospectively assessed and recorded. The definite diagnosis of fetal Hb Bart's disease was based on DNA analysis (chorionic villus sampling) or subsequent fetal Hb typing (high‐performance liquid chromatography; cordocentesis). Results Among 104 pregnancies at risk with complete sonographic assessment at 11 to 14 weeks of gestation, 30 fetuses were finally proven to be affected. The CT ratio gave the highest sensitivity, 93.3%, with specificity of 93.2%, followed by placental thickness and MCA‐PSV, respectively. Nuchal translucency had a very low sensitivity of 16.7%. The combination of CT ratio and MCA‐PSV increased the sensitivity to 96.7% but somewhat compromise specificity. Conclusions At 11 to 14 weeks of gestation, sonographic markers can effectively differentiate affected from unaffected pregnancies. The most sensitive marker was CT ratio plus MCA‐PSV. Of couples at risk with no any sonographic markers, the risk of having an affected fetus is nearly eliminated. © 2013 John Wiley & Sons, Ltd.